Determinantes da taxa de juros do financiamento agrícola brasileiro - Fernandes, Paloma Regina Wolf (2019)
Agricultural financing in Brazil represents one of the main instruments of the country's agricultural policy. Its origin may be public or private and its resources may be classified as controlled (with subsidized interest rates) or uncontrolled (with free market interest rates). Private rural credit represents a financial intermediation and has the participation of agents belonging to the agribusiness production chains. In addition, agricultural financing has been experiencing significant growth since the 1980s, when there was a public finance crisis. Its expansion, although positive in terms of the expansion and diversification of the supply of resources, reflects the restriction of resources of public sources. The general objective of the study, therefore, is to identify the possible determinants of the free interest rate of Brazilian agricultural financing. The method used was a vector autoregression model - VAR, whose proposed variables are: Selic policy rate; exchange rate; default of borrowers; and a base index of agricultural commodity prices. Except for the exchange rate, all variables had explanatory power over the rural credit free interest rate, with Selic being its main determinant.